Les assurances relatives aux immeubles en copropriété : caractéristiques et distinctions - Moreau, Rémi (Assurances, 1982)
Co-ownership of real estate is a form of ownership which has social, financial and legal consequences. Co-ownership is becoming more popular in Canada, U.S.A. and Europe. Although it would appear to be straightforward, it causes certain problems regarding insurance. Me Remi Moreau's article discusses these problems and describes insurers' attitude to them and their general approach. Mr. Moreau points out that insurance wordings are often inadequate to take care of the agreements between co-owners.